Peningkatan Keterampilan Proses Sains dan Prestasi Belajar Siswa Menggunakan Model Pembelajaran Carousel Feedback diPadukan Metode Fish Bowl - Rahidhatul Laila Agustina; Rifda Mardian Arif (JURUSAN PENDIDIKAN GURU SEKOLAH DASAR, 2020)
The purpose of this study was to escribe science learning using a carousel feedback learning model combined with the fishbowl method to improve the learning achievement of fifth grade students at SDN Cahaya Baru in Jejangkit District, Barito Kuala Regency. This type of research is classroom action research ( PTK ) , is collaboration . Data collection techniques used were interviews , observation and tests .The results of the data analysis showed the implementation of the first cycle of lesson plan 1, the average percentage of lesson plan implementation was 96% (very good category), the first cycle of meeting 2 the percentage of lesson plan implementation was 100% (very good category), and second cycle meeting 3 percentage of implementation RPP of 99% (very good category). The implementation of science process skills of students based on student activities at the first meeting was obtained 96.75% with good categories, meeting II was 97% with good categories and meeting III was 96.75% with very good categories. Increasing student learning achievement both individually and classically from the first cycle is 35% and increases to 94% in the second cycle. It can be concluded that the use of the feedback carousel learning model combined with the fish bowl method can improve the science learning achievement of fifth grade students at Cahaya Baru Elementary School 2018/2019.